Transformational Leadership of School Principals in Shaping School Culture and Improving Student Achievement in Elementary Schools - Asriyah, Masfiyatul (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to examine the role of the principal’s transformational leadership in shaping school culture and improving student achievement at SDI Pelangi Bandar Lampung. The study is grounded in the need to understand how school leadership can create a conducive learning environment and directly influence students’ academic outcomes, particularly within the context of private primary schools, which remain relatively under-researched. Diverse human resources, unequal teacher capacity, and a school culture that is not yet fully adaptive to change often become obstacles in achieving optimal educational outcomes. This research employs a qualitative approach with a case study design. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing interactively. The practices implemented by the principal successfully fostered a safe, welcoming, collaborative, and achievement-oriented school culture. This strong school culture directly contributed to increased learning motivation, discipline, and student participation in both academic and non-academic activities. The study concludes that transformational leadership plays a crucial role in shaping a positive school culture and directly enhancing student achievement at SDI Pelangi Bandar Lampung. Within the dimension of intellectual stimulation, the implementation of Project-Based Learning, the use of learning corners, and opportunities for classroom experimentation demonstrate that innovation has become an integral part of the school culture. This support has improved instructional effectiveness and heightened student enthusiasm for academic activities. Meanwhile, the dimension of individualized consideration is reflected through mentoring, coaching, and clinical supervision provided by the principal to teachers. This personalized approach has increased teacher confidence, reduced emotional barriers in teaching, and strengthened interpersonal relationships within the school environment.